2015
DOI: 10.1080/14763141.2015.1024717
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the bend on technique and performance during maximal effort sprinting

Abstract: This study investigated changes in performance and technique that occur during maximal effort bend sprinting compared with straight-line sprinting under typical outdoor track conditions. Utilising a repeated measures design, three-dimensional video analysis was conducted on seven male sprinters in both conditions (bend radius: 37.72 m). Mean race velocity decreased from 9.86  to 9.39 m/s for the left step (p = 0.008) and from 9.80  to 9.33 m/s for the right step (p = 0.004) on the bend compared with the straig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
229
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(260 citation statements)
references
References 29 publications
28
229
3
Order By: Relevance
“…They suggested that swing time would remain constant and, therefore, step frequency would decrease. The increased left step ground contact time in the present study is in line with previously reported increases of 11 ms in left step ground contact time during maximal effort bend sprinting (Churchill et al., ). Alt et al.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…They suggested that swing time would remain constant and, therefore, step frequency would decrease. The increased left step ground contact time in the present study is in line with previously reported increases of 11 ms in left step ground contact time during maximal effort bend sprinting (Churchill et al., ). Alt et al.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Churchill et al. () reported that the right hip abduction/adduction angle at touchdown was not significantly affected by the bend and that peak adduction was less on the bend compared with the straight. The inward lean and abduction/adduction angles could also influence why there were statistically significant differences in horizontal braking impulses between left and right step on the bend (left step braking larger) and between the straight and bend conditions for the left leg (bend condition larger).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations